Reshaping Healthcare: A Bibliometric Analysis of Lessons Learned in Post-COVID-19 Health Policy - Azizan, Azliyana; Abdullah, Khairul Hafezad; Rahayu, Sri Ratna; Rusli, Nadia Safirah; Tarmidzi, Nornajehah (Kesmas, 2023)
The COVID-19 pandemic has profoundly impacted health policy globally, leading to heightened concern and urgency. However, previous studies have been hampered by limited resources and insufficient discussions on the long-term implications for health policies following multiple COVID-19 waves. Thus, this study examined the evolution of international studies on post-COVID-19 health policy. A comprehensive analysis used well-known literature databases Scopus and Web of Science to explore parameters including publication growth, participating countries, areas of interest, and keyword analysis of topics such as"COVID-19" and "Health Policy." The United States emerged as an active participant, focusing on "Computer science." Key themes included "COVID-19 Pandemic," "Public health policy," and "Epidemiology," highlighting current trends. It emphasized the significance of global cooperation and knowledge exchange in addressing the complex challenges posed by the pandemic and shaping resilient health policies for the future. The contribution of this study lies in providing a comprehensive overview of post-COVID-19 health policy research and its implications for the health field.